Percepções de um grupo de mulheres sobre o pilates: do pré-natal ao pós-parto imediato - Souza, Pauliana Carolina de (2017)
Introduction: The Policy on Integral Attention to Women's Health (PAISM) proposes the improvement of reproductive health care, and provides for the qualification of health services to meet the specific needs of women, including the humanization of care during all phases of life. Pregnancy is a period of major physical changes to which the pregnant woman may have the tools to adapt to or ameliorate them. The Pilates method, considered a safe and effective physical exercise, can offer the benefits that the pregnant woman needs to promote her health at this stage with regard to musculoskeletal changes. Objectives: To know the perception of a group of women about the practice of Pilates during pregnancy, in childbirth and immediate postpartum. Methods: This is a qualitative, descriptive study that used participant observation during the Pilates sessions with a group of pregnant women and records in their charts about their reports about their impressions regarding pregnancy and even about activities Which were proposed during the sessions, as well as postpartum interview on the practice of Pilates in gestation and experiences of childbirth and immediate postpartum. Results: The participants' perception was positive regarding the benefits of Pilates during pregnancy and for the experience of childbirth and in the immediate postpartum period. Participants reported relief of pain, increased relaxation during pregnancy, as well as facilities for performing daily life activities. They also reported that Pilates exercises provided some benefits for childbirth, such as shorter labor time, easier vaginal delivery, and even among participants who had a cesarean birth, reported that the exercises benefited them later in physical recovery. Conclusion: The good result of the practice of Pilates in pregnancy suggests a change in the health care of the pregnant woman by health professionals, with the objective of encouraging them to practice the method during the gestational period, allowing her to live with the discomforts Which this period causes with more quality of life.